Franciscanos no Brasil: uma história silenciada - Santos, Edgar Araujo Alves dos (2019)
This dissertation will analyze the formation of the historiographic silence about the performance of the Order of the Friars Minor in Brazil. For this, we will observe the historiographic production regarding the Franciscans' performance in Brazil, seeking to analyze why the Friars Minor lost space in the historical memory of the population. From the studies carried out around the subject, the actions of the order and its historiographic productions will be evaluated in the colonial period, contrasting its missionary expansion with the historical reference about the Franciscan performance in Brazil. This will allow us to follow the dialectic of the relations established between the Franciscan religious body and the historiographic production related to the actions of catechization in the Brazilian territory. This study has as its premise to collaborate to reflect on the historical and religious processes, in a perspective of Study of Religions, which include territorial and missionary expansion in Brazil, gathering texts of historical analysis, written documents, Secondary sources and images, which are added to reading, allowing a broad understanding of the insertion of the Franciscan Order in the development process of Brazil